2020
DOI: 10.1186/s12991-020-00304-4
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive impairment and evidence-based treatment options in Bipolar disorder

Abstract: Background The current paper briefly summarizes the literature on the neurocognitive deficit and its treatment in BD patients. Methods The material was chosen on the basis of previous systematic reviews the author has taken part in. Results The data so far suggest that the deficit is qualitatively similar but quantitatively milder in comparison to schizophrenia, it is pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 134 publications
2
7
0
Order By: Relevance
“…The finding of worse sustained attention in the BD CB− group versus HC converges with prior studies of adolescents and adults with BD (Fountoulakis, 2020; Kolur et al, 2006). While not statistically significant, Figure 2 depicts a visual trend toward better sustained attention in the BD CB+ group versus BD CB− ( p = 0.32) and HCs ( p = 0.26).…”
Section: Discussionsupporting
confidence: 86%
“…The finding of worse sustained attention in the BD CB− group versus HC converges with prior studies of adolescents and adults with BD (Fountoulakis, 2020; Kolur et al, 2006). While not statistically significant, Figure 2 depicts a visual trend toward better sustained attention in the BD CB+ group versus BD CB− ( p = 0.32) and HCs ( p = 0.26).…”
Section: Discussionsupporting
confidence: 86%
“…Clinical and macro-imaging studies have shown that cognitive impairment is a pivotal symptom in patients with BPD; similar findings have been obtained with animal models of depression or mania [ 90 94 ]. Our finding that cognitive impairment was more severe in the manic phase provides a new clue for investigation of this difficult-to-improve symptom in patients with BPD, although it may have been influenced by confounding factors.…”
Section: Discussionsupporting
confidence: 61%
“…In some cases, electroconvulsive therapy (ECT) is recommended as a highly and rapidly effective treatment for the management of serious acute manic episodes [1]. Although some studies have reported that Li and ECT (Li-ECT) combined treatment is safe and more effective than either Li or ECT alone for both depression [2] and mania [3], opposing views have implied that Li-ECT may increase the risk of cognitive impairment and delirium [4,5]. Here, we report a case of BD where the patient developed delirium and reversible pure anomic aphasia after Li-ECT treatment.…”
Section: Introductionmentioning
confidence: 99%